A Comparison of High School Graduation Predictors Between Two Ontario Student Cohorts - Robson, Karen; Malette, Nicole; Anisef, Paul; Maier, Reana; Brown, Robert (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
While a number of factors have already been shown to impact variations in graduation rates among students in Canada, there is little research examining the changing impact of these factors on Ontario students’ secondary education completion over time. This research draws on data from two Grade 9 cohorts (2006 and 2011) from the Toronto District School Board in order to unpack how predictors of high school graduation change over time. In particular, we use multivariate analysis to examine whether predictors (including gender, race, parental education, household income, suspension, academic achievement, special education needs, and Grade 9 absenteeism) are significant by cohort of students and if there are gaps in secondary school success between subgroups. Findings demonstrate that high school completion is increasing over time and that there is a diminishing importance of parental education and neighbourhood household income as a predictor of high school graduation. However, we do find evidence of persistent under-achievement among students of certain racial backgrounds, lower academic streams, and those with high rates of absenteeism. We argue that additional data infrastructure in Ontario and beyond are necessary to identify how our findings generalize to the province as a whole.